Discussing medicine and law in Maribor / Razprave o medicini in pravu v Mariboru - Vesna Rijavec; Jelka Gorišek; Vojko Flis (Acta Medico-Biotechnica, 2021)
The combined discipline of medicine and law is dealt with very differently among different countries. As a result, the comparison between individual legal systems in the interdisciplinary area of law and medicine is complicated (1, 2, 3). In some European universities, this subject is taught as a separate course in law departments because of its extensivenessand complexity. In Slovenia, however, this subject was initially discussed in depth in gatherings of medical and legal experts at regular international meetings in Maribor, with this year marking the twentieth such discussion. The annual international medicine-law gatherings in Maribor are intended for discussion of topics where the two fields of knowledge meet. Sometimes the participants’ views are joined by views from other fields. The selection of discussion topics is dictated by relevant issues requiring clarification and analysis before successful solutions can be found. In this article, we show what the main guidelines were for discussions at such meetings and their effect on the development of medical law in Slovenia.